Oxygen activity changing when simulating silicon filtering process - Mekhtiyev (Mekhtiev) A. D. Ali Dzhavanshirovich; Zholdubaeva Z. Kh.; Issin B. D.; Golovacheva V. N.; Yurchenko A. V. Aleksey Vasilievich; Issin D. K. (2016, 2016)
In the article there is considered the efficiency of using filters for the refinement of metal melts, the use of filters in metallurgical practice and research of the inoculating mechanism of filter refinement of a metal melt from the dissolved impurities. In the inoculating mechanism the surface of the filter serves as a substrate for separation on it thenonmetallic phase directly from the melt, passing the stage of its separation into an isolated particle. This is proved experimentally, by monitoring the change of the deleted impurity activity by the EMF (electromotive force) method.